A Strategy for Gaining Comprehension : Question â Answer Relationship (QAR) - Ali, Ahmad Rasyid; Nisa, Muhajiratun (Reflective, 2014)
Having reading skill is fundamental factor responsible for increasing ability to learn and master alrge amounts of information. There is a significant correlation between reading and academic success. It can be said that a student who can do well in reading is possible to succed in school better than one who is a poor reader. They can obtain what is important from the particular writing they are working on. In fact, one basic problem which L2 learners usually try to grapple with is the innability to comprehen their reading materials duc to lack of have. Therefore, quetion and answer relationship (QAR) strategy is proposed to aid readers for comprehension. Keyword : strategy, QAR, reading comprehension.